Eikonal equation-based seismic tomography of the source areas of the 2008 Mw 7.9 Wenchuan earthquake and the 2013 Mw 6.6 Lushan earthquake - Li, Jun (2021)
We use the eikonal equation-based seismic travel-time tomography method to image the source areas of the 2008 Wenchuan earthquake and the 2013 Lushan earthquake in the Longmenshan fault zone. High-resolution Vₚ and Vₛ models are obtained by inverting 75,686 P-wave and 74,552 S-wave travel times of local earthquakes during the period from 2009 to 2018. The tomographic models reveal strong crustal velocity heterogeneities in the study area. A significant velocity contrast exists across the Longmenshan fault zone: The western Songpan–Ganzi block is a high-velocity body, whereas the eastern Sichuan basin is a low-velocity anomaly. The hypocenter of the 2008 Wenchuan earthquake is between a high-velocity and a low-velocity anomaly. Beneath the Wenchuan mainshock, there is a significant low-velocity structure in the lower crust. The 2013 Lushan earthquake occurred in rocks associated with a high-velocity anomaly. A distinct low-velocity zone with low seismicity is imaged between the 2008 Wenchuan earthquake and the 2013 Lushan earth-quake, where the crustal ductile deformation is likely to occur. The Baoxing complex to the northwest of the Lushan hypocenter exhibits as a high-velocity anomaly, which may be a carrier of stress accumulation and more prone to seismic activities in the future.